Hubungan Single Leg Static Dengan Functional Balance Pada Remaja - Reza, Muhammad; , Dwi Rosella Komala Sari, SSt.FT.,M.Fis (2016)
Recently, in this era, adolescent tend to do less physical activity that will lead an effect on the sensory input coordination of visual, vestibular and somatosensory. If this system works well, it will take effect when given certain instructions, for example on the single static exercise and fuctional balance exercise, in which these exercise requires good coordination.The purpose of this study was to determine the relationship of single leg static and functional balance balance on adolescents. This study was an observational study with cross sectional design. The samples used were 35 adolescents who live in the dormitory of FKIP PGSD UNS. Single leg static measurements was performed by using COP, meanwhile, the fuctional balance measurements was performed by using Star excursion balance test (SEBT). The results of the analysis on the relationship of Single Leg Static and Fuctional balance which was performed by using statistical analysis Chi-square or Chi-squared (χ²) indicated p value 0.006 and OR 9,853 for single leg static and functional balance of the right leg and p value 0.000 and OR 22,626 for single leg static and functional balance of the left leg Based on the analysis, it can be concluded that there is a significant relationship of Static Single Leg and Functional balance on adolescents